2023
DOI: 10.1002/1873-3468.14586
|View full text |Cite
|
Sign up to set email alerts
|

The catalytic domains of all human KDM5 JmjC demethylases catalyse N‐methyl arginine demethylation

Abstract: The demethylation of N e -methyllysine residues on histones by Jumonji-C lysine demethylases (JmjC-KDMs) has been established. A subset of JmjC-KDMs has also been reported to have N ω -methylarginine residue demethylase (RDM) activity. Here, we describe biochemical screening studies, showing that the catalytic domains of all human KDM5s (KDM5A-KDM5D), KDM4E and, to a lesser extent, KDM4A/D, have both KDM and RDM activities with histone peptides. Ras GTPase-activating protein-binding protein 1 peptides were sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…A recent in vitro study reported that KDM5 proteins are capable of arginine demethylation (RDM) on H3 and H4 peptides. It was shown that the catalytic domain of all four members of the KDM5 family, including KDM5A, is capable of demethylation of H3R2me2a residues on peptide substrate in vitro [ 44 ]. However, in vivo confirmation of KDM5A’s involvement on H3R2me2a is yet to be proven.…”
Section: Activity Of Kdm5a Proteinmentioning
confidence: 99%
“…A recent in vitro study reported that KDM5 proteins are capable of arginine demethylation (RDM) on H3 and H4 peptides. It was shown that the catalytic domain of all four members of the KDM5 family, including KDM5A, is capable of demethylation of H3R2me2a residues on peptide substrate in vitro [ 44 ]. However, in vivo confirmation of KDM5A’s involvement on H3R2me2a is yet to be proven.…”
Section: Activity Of Kdm5a Proteinmentioning
confidence: 99%